Resiliência, religiosidade e sentido de vida em mulheres com câncer de mama - Amaro, Luana da Silva (2014)
The breast cancer continues to be one of the top causes of death of female people in the world, even with the great therapeutic advancements. In Brazil, it has been the biggest cause of death in the female population, mainly in the age group between 40 and 69 years. Beyond the incidence of the infirmity, in the last decades, the characteristics of the treatment are also expressive, what demands, sometimes, a considerable period of hospitalization or forwards and backwards to the hospital, exposes the patient to diverse invasive procedures, which are painful and unpleasant in the physical and emotional ranges. Thus, the objective of this study is to investigate the factors that can promote a resilient behavior in patients with breast cancer, to verify with the patients the forms of confrontation in the face of beliefs, behaviors and affections in relation to the pathology and to the treatment and to analyze the possible relations between religiosity and life sense in the confront of the disease. It is an exploratory and descriptive research with a qualitative and quantitative approach. The instruments used to data collection were: the social demographic and clinic data questioning; the Coping Religioso and Espiritual Abreviada scale - CRE BREVE, the Life Sense Questioning; the Semi-Structured interview based on the modality of thematic oral history and the Field Diary. The sample was composed by 50 patients of two non-governmental organizations placed in the city of João Pessoa-PB, with 46,34 age average. The diagnostic time was between 2 and 6 months (62%) and between 7 and 12 months (38%), and they were having therapeutic treatments: 28% was receiving chemotherapy; 24% hormontherapy; 16% radiotherapy and 4% were realizing the immunotherapy, after to be, or not, submitted to mastectomy. The results pointed as factors of Resilience in the present study: the support from family, friends and the support Group to woman with cancer; the perception that other people need them and the spirituality/religiosity, which are grouped as realization of living values. The patients were able to redefine the moment they were living, transforming the personality characteristics and the world vision, achieving the realization of attitudinal values, finding sense in front of the inevitable suffering. It was evident that the participants used a higher grade of Coping Religioso and Espiritual positive (M= 3,3 DP = 0,6) which contemplates strategies that provide benefic/positive effect to the practitioner, however, they used the Coping Religioso and Espiritual negative in lesser extent (M= 1,7 DP= 0,7). The results also pointed a higher realization of sense (M=6,0 DP=0,8). Indicating that the participants despite living the process or breast cancer, could perceive sense in life. Some correlations between the Coping Religioso and Espiritual and the Life Sense were found: the positive dimension of this scale, which approaches the spiritual seeking care, was correlated positively with the factor sense seeking (r = 0,2; p<_0,05), as well as there was a correlation between the factor age and the positive dimension of CRE: Offer to help others, (r=0,2; p<0,05). It concludes that the spirituality/religiosity in this sample, favored a new perception referent to the breast cancer, beyond well-being and hope, and it contributed to the resignification of the participants life.